2004
DOI: 10.1002/jsfa.1983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cultivar, root weight, storage and boiling on carbohydrate content in carrots (Daucus carota L)

Abstract: The effects of cultivar (n = 4), root weight (n = 4), storage (5 months) and boiling (7 min) and their interactions on the content of dry matter and carbohydrates were studied and ranked in carrots. Boiling had the greatest effect and had an influence on all variables except the ratio between sucrose and the monosaccharides glucose and fructose. The choice of cultivar was also of great importance as regards glucose, fructose and sucrose content, while dietary fibre and dry matter were much less affected, or ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…Machewad et al [36] reported total soluble sugar losses of 62.5 % in the conventional blanching of carrots carried out in boiling water for 5 min, whereas Nyman et al [37] found 24 and 38 % losses of soluble solids and carbohydrates, respectively, in carrots blanched in boiling water for 7 min. All these differences might be attributed, among other factors, to the different sample geometry and water/sample ratio used in the reported studies.…”
Section: Resultsmentioning
confidence: 97%
“…Machewad et al [36] reported total soluble sugar losses of 62.5 % in the conventional blanching of carrots carried out in boiling water for 5 min, whereas Nyman et al [37] found 24 and 38 % losses of soluble solids and carbohydrates, respectively, in carrots blanched in boiling water for 7 min. All these differences might be attributed, among other factors, to the different sample geometry and water/sample ratio used in the reported studies.…”
Section: Resultsmentioning
confidence: 97%
“…The loss of terpene and sesquiterpene volatiles along with changes in the carbohydrate fraction during the thermal process and storage of carrot can alter its characteristic organoleptic properties 9, 18, 19. Although the effect of different preservation processes and drying techniques on major carrot sugars (fructose, glucose and sucrose) has been extensively studied,20–22 no data have been reported on changes in minor carrot carbohydrates with the different stages of dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…lignin) (Darmanyan, 1996;Ng and Waldron, 1997;Ng et al, 1998;Gómez Galindo et al, 2004;Toivonen and Brummell, 2008), carrot plant physiology (Hasselbring, 1927), and the growth/development of carrot roots (Rosenfeld et al, 2002) have also been studied. Additionally, a wide range of information is available regarding the effect of cooking, boiling, blanching (Ng and Waldron, 1997;Svanberg et al, 1997;Nyman et al, 2005) and processing (e.g. peeling) (Bolin and Huxsoll, 1991;Howard and Griffin, 1993;Rodríguez-Sevilla et al, 1999;Gamboa-Santos et al, 2013) in carrot nutritional constituents, fresh carrot quality, and appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has gone into examining the dietary fiber (Nyman et al, 2005), carbohydrate (Rodríguez-Sevilla et al, 1999;Suojala, 2000;Nyman et al, 2005;Baranski et al, 2012;Bufler, 2013), solutes (Korolev et al, 2000), and pigment (carotenoid) (Sood et al, 1993;Tsukakoshi et al, 2009;Baranski et al, 2012) content in different carrot cultivars, with the main objective of assessing their nutritional attributes. In addition, changes in carrot cell wall content and biochemical bases (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation